5x-2(3x+6)=5x-2(3x+5)

Simple and best practice solution for 5x-2(3x+6)=5x-2(3x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-2(3x+6)=5x-2(3x+5) equation:



5x-2(3x+6)=5x-2(3x+5)
We move all terms to the left:
5x-2(3x+6)-(5x-2(3x+5))=0
We multiply parentheses
5x-6x-(5x-2(3x+5))-12=0
We calculate terms in parentheses: -(5x-2(3x+5)), so:
5x-2(3x+5)
We multiply parentheses
5x-6x-10
We add all the numbers together, and all the variables
-1x-10
Back to the equation:
-(-1x-10)
We add all the numbers together, and all the variables
-1x-(-1x-10)-12=0
We get rid of parentheses
-1x+1x+10-12=0
We add all the numbers together, and all the variables
-2!=0
There is no solution for this equation

See similar equations:

| q+69=81 | | (-4)(x)=(1/2)x+1 | | 10x-5(x-2)=20 | | b+11=37 | | x-6=x/18 | | 3(x)=5x+1 | | f+31=57 | | y+6=88 | | 6d−14=34 | | 4p+5=377 | | 6.52+8.4t+9.5t=-3.84+3.1t | | -47=5x-3(x+19) | | 27=1-5x+6 | | 3(5−2n)+9n=-12 | | (3c-12)=-9 | | 1-5f=5-7f | | (x)=(1/2)x+1 | | 3(2x+4)+6(x+2)=48 | | 27=1-5x | | 8h+5=2 | | 75=5(t-70) | | 8u+10=9u-1+1 | | -(m-7)=15 | | b−36=35 | | x^2-3x+9=31 | | 4g/2=50 | | -152=-8x-7(8-8x) | | 4x+18-6x-40=-68 | | 1=w+2/4 | | 34=9-5f | | 8k+3k-2=9k-4 | | x^2+8x+19=8 |

Equations solver categories